Dry granular ceramic tile and preparation method thereof
By mixing dry-grain glaze and surface glaze with high silicon-aluminum content, a stable crystal structure is formed, which solves the problem of temperature requirements in traditional ceramic production, and achieves the stability of ceramic quality and the reduction of production costs.
Patent Information
- Application Number
- CN202411791470.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-06
- Publication Date
- 2025-03-11
AI Technical Summary
During the production process of traditional ceramics, temperature requirements are demanding, and external temperature fluctuations and humidity interference lead to a decline in the quality of ceramics, increasing production costs.
Dry-grain ceramic tiles and their preparation methods are used to form a stable crystal structure by mixing dry-grain glaze and surface glaze glaze with high silicon-aluminum content to reduce the dependence on external temperature.
Ceramics fired at large temperatures have the same properties, reducing production costs and improving the anti-fouling, wear and slip properties of ceramic tiles.
Smart Images

Figure CN119591425A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of ceramic tiles, and in particular to a dry granular ceramic tile and a preparation method thereof. Background Art
[0002] With the progress of society, people have higher and higher requirements for the cost-effectiveness of the selection of decoration materials. Ceramics, as a part of the main body of decoration, naturally also need to pursue high-quality products. Therefore, ceramic surface auxiliary materials must be iteratively upgraded. With the help of ceramic auxiliary materials, ceramic products are becoming more and more diverse. Especially in recent years, with the application of dry particles, the decorative performance and physical application performance of the products have been greatly improved.
[0003] Ceramic tiles have become the main product of home decoration due to their excellent physical properties. With the wide application of ceramic tiles, ceramic tiles with special effects are emerging in an endless stream. In the traditional ceramic production process, different ceramic tiles have different and stringent temperature requirements. During the firing process, small-scale temperature fluctuations in the kiln and interference from external weather and humidity will cause defects in the produced ceramics, reducing product quality. Therefore, providing a ceramic tile that is not affected by external temperature conditions during the firing process can effectively reduce production costs. Summary of the invention
[0004] The present invention aims to overcome at least one defect of the above-mentioned prior art and provide a dry particle ceramic tile and a preparation method thereof, so as to achieve the effect of reducing the production cost of ceramics.
[0005] One of the purposes of the present invention is to provide a dry granular ceramic tile, which comprises, from bottom to top, a body layer, a surface glaze layer, a printing layer and a dry granular glaze layer, wherein the raw material of the dry granular glaze layer comprises dry granular glaze, and the raw material of the surface glaze layer comprises surface glaze;
[0006] The chemical composition of the dry granular glaze, in terms of weight percentage, includes: 58-65 parts of SiO2, 15-20 parts of Al2O3, 4.5-6.5 parts of K2O, 5-8 parts of CaO, 0.65-1.56 parts of SrO, 6-8 parts of Na2O, 0.5-0.96 parts of ZnO, 0.5-1.2 parts of MgO, and 1-3 parts of ZrSiO4;
[0007] The chemical composition of the glaze, calculated by weight percentage, includes: 50-58 parts of SiO2, 20-28 parts of Al2O3, 3-5 parts of CaO, 3-8 parts of SrO, 2-4 parts of ZnO, 0.01-0.03 parts of TiO2, and 1-3 parts of BaO.
[0008] In this solution, the total weight ratio of SiO2 and Al2O3 in the dry granular raw materials and the glaze material is more than 70 parts. By adjusting the silicon and aluminum content in the formula, it is ensured that during the firing process, the crystal structure of the silicon, aluminum and zinc supporting the dry granules can form a common phase crystal during high-temperature firing, forming a stable crystal structure. The formula with high silicon and aluminum content can ensure the stability of the dry granules during the firing process, reduce the degree of influence by external temperature, and the ceramics fired at a wide range of temperatures have the same properties, and the production conditions are less limited.
[0009] Preferably, the raw materials of the dry granular glaze include, by weight: 17-20 parts of aluminum oxide, 8-12 parts of calcite, 5-6 parts of potassium carbonate, 8-12 parts of soda ash, 45-56 parts of quartz powder, 0.5-1 parts of zinc oxide, 1-2 parts of strontium carbonate, and 2-4 parts of dolomite.
[0010] Preferably, the raw materials of the surface glaze include, by weight: 15-22 parts of selected potassium feldspar, 5-10 parts of air knife clay, 15-25 parts of sodium feldspar, 10-20 parts of nepheline powder, 3-10 parts of wollastonite powder, 5-16 parts of aluminum oxide, 12-17 parts of quartz powder, 5-10 parts of zirconium silicate, 1-3 parts of zinc oxide, 5-10 parts of 1816 frit, 0.2-0.5 parts of sodium tripolysulfate, and 0.1-0.2 parts of sodium methyl cellulose.
[0011] Furthermore, the main components of the selected potassium feldspar are 65-68% SiO2, 16-18% Al2O3, and 13-15% K2O; the 1816 frit includes, by weight: 43-49 parts of SiO2, 24-26 parts of Al2O3, 4-5 parts of K2O, 3-5 parts of Na2O, 4-7 parts of CaO, 0.5-1 parts of Li2O, 4-5 parts of SrO, and 8-10 parts of ZnO.
[0012] Preferably, the particle size of the dry granular glaze is 50um-100um.
[0013] The dry granular glaze has a small particle size, is compactly packed, has good anti-fouling and anti-slip properties, and has good wear resistance.
[0014] Preferably, the glossiness of the tile surface is 10-20 degrees.
[0015] The glossiness of the ceramic tile surface is between 10-20 degrees, which makes the ceramic tile surface warm and transparent, and the texture is better than traditional ceramic tiles. Compared with traditional ceramic tiles, the higher the glossiness, the more delicate it feels, and the lower the glossiness, the rougher it feels. This method of making ceramic tiles can provide low-gloss and delicate tiles to meet the pursuit of more consumer groups.
[0016] The second object of the present invention is to provide a method for preparing the above-mentioned dry particle ceramic tile, comprising the following steps: after water spraying a dried green body, applying a glaze material and an inkjet printing pattern on the surface of the green body in sequence; applying a dry particle glaze slurry on the surface of the green body containing the printed pattern, firing, and grinding the edges to obtain the dry particle ceramic tile;
[0017] The dry granular glaze slurry comprises dry granular glaze, a suspending agent, a protective glaze, a defoaming agent and water.
[0018] Preferably, the preparation method of the dry granular glaze comprises:
[0019] Mixing the raw materials for preparing the dry granular glaze according to weight proportions, and firing the mixture to obtain a fired product;
[0020] The fired product is cooled and crushed to obtain a dry granular semi-finished product;
[0021] The dry granular semi-finished product is treated at a temperature of 850° C. to 950° C. to obtain a dry granular glaze.
[0022] Furthermore, the step of processing the dry granule semi-finished product is: subjecting the dry granule semi-finished product to high-temperature heating in a heating device in a free-falling manner.
[0023] Preferably, the kiln firing temperature is between 1180°C and 1210°C.
[0024] Compared with the prior art, the present invention has the following beneficial effects:
[0025] 1. The present invention ensures the stability of dry particles during firing by adjusting the silicon and aluminum content in the formula, reduces the degree of influence by external temperature, reduces the production limitations of the obtained ceramics, and reduces the production cost of the ceramics.
[0026] 2. The dry particles in the formula of the present invention have a small particle size, are densely packed, have good anti-fouling and wear resistance, and have good anti-slip properties. After firing, the brick surface is smooth and fine.
[0027] 3. The surface glossiness of the ceramic tile of the present invention is between 10-20 degrees. The surface of the ceramic tile is warm and transparent, feels delicate and smooth, and has a texture better than traditional ceramic tiles. The ceramic tiles made by this method can provide low-gloss and delicate ceramic tiles to meet the pursuit of more consumer groups.
[0028] 4. Low-gloss ceramics usually have poor surface stain resistance and anti-slip properties. The ceramics of the present invention have a gloss between 10-20 degrees and can also have good stain resistance and anti-slip properties, taking into account both low gloss and stain resistance, and are suitable for various application scenarios. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] Figure 1 This is a picture taken on the surface of the ceramic tile of Example 1.
[0030] Figure 2 This is a picture taken on the surface of the ceramic tile of Example 2.
[0031] Figure 3 This is a picture taken on the surface of the ceramic tile of Example 3.
[0032] Figure 4 This is a picture taken on the surface of the ceramic tile of Example 4.
[0033] Figure 5 This is a picture taken on the surface of the tile of Comparative Example 1.
[0034] Figure 6 This is a picture taken on the surface of the ceramic tile of Comparative Example 2.
[0035] Figure 7 This is a picture taken on the surface of the ceramic tile of Comparative Example 3. DETAILED DESCRIPTION
[0036] One of the purposes of the present invention is to provide a dry granular ceramic tile, which comprises, from bottom to top, a body layer, a surface glaze layer, a printing layer and a dry granular glaze layer, wherein the raw material of the dry granular glaze layer comprises dry granular glaze, and the raw material of the surface glaze layer comprises surface glaze;
[0037] The chemical composition of the dry granular glaze, in terms of weight percentage, includes: 58-65 parts of SiO2, 15-20 parts of Al2O3, 4.5-6.5 parts of K2O, 5-8 parts of CaO, 0.65-1.56 parts of SrO, 6-8 parts of Na2O, 0.5-0.96 parts of ZnO, 0.5-1.2 parts of MgO, and 1-3 parts of ZrSiO4;
[0038] The chemical composition of the glaze, calculated by weight percentage, includes: 50-58 parts of SiO2, 20-28 parts of Al2O3, 3-5 parts of CaO, 3-8 parts of SrO, 2-4 parts of ZnO, 0.01-0.03 parts of TiO2, and 1-3 parts of BaO.
[0039] In this embodiment, the proportion of SiO2 and Al2O3 in the total weight of the dry granular glaze and the surface glaze is relatively high. The present invention adjusts the silicon and aluminum content in the formula to ensure that during the firing process, the crystal structure supporting the dry granular silicon, aluminum and zinc can form a common phase crystal during high-temperature firing to form a stable crystal structure. The formula with high silicon and aluminum content can ensure the stability of the dry particles during the firing process, reduce the degree of influence by the external temperature, and the ceramics fired at a wide range of temperatures have the same properties, and the production conditions are less limited. When the silicon and aluminum content is lower or higher than the range, it will lead to large limitations on the production conditions of the tiles, and the stain resistance and anti-slip degree will be reduced.
[0040] In some embodiments, the raw materials of the dry granular glaze include, by weight: 17-20 parts of aluminum oxide, 8-12 parts of calcite, 5-6 parts of potassium carbonate, 8-12 parts of soda ash, 45-56 parts of quartz powder, 0.5-1 parts of zinc oxide, 1-2 parts of strontium carbonate, and 2-4 parts of dolomite.
[0041] In some embodiments, the raw materials of the glaze include, by weight: 15-22 parts of selected potassium feldspar, 5-10 parts of air knife clay, 15-25 parts of sodium feldspar, 10-20 parts of nepheline powder, 3-10 parts of wollastonite powder, 5-16 parts of aluminum oxide, 12-17 parts of quartz powder, 5-10 parts of zirconium silicate, 1-3 parts of zinc oxide, 5-10 parts of 1816 frit, 0.2-0.5 parts of sodium tripolysulfate, and 0.1-0.2 parts of sodium methyl cellulose.
[0042] In specific implementation, the main components of the selected potassium feldspar are 65-68% SiO2, 16-18% Al2O3, and 13-15% K2O; the 1816 frit includes, by weight: 43-49 parts of SiO2, 24-26 parts of Al2O3, 4-5 parts of K2O, 3-5 parts of Na2O, 4-7 parts of CaO, 0.5-1 parts of Li2O, 4-5 parts of SrO, and 8-10 parts of ZnO.
[0043] Preferably, the particle size of the dry granular glaze is 50um-100um.
[0044] The dry granular glaze has a small particle size, is compactly packed, has good anti-fouling and anti-slip properties, and has good wear resistance.
[0045] Preferably, the glossiness of the tile surface is 10-20 degrees.
[0046] The glossiness of the ceramic tile surface is between 10-20 degrees, which makes the ceramic tile surface warm and transparent, and the texture is better than traditional ceramic tiles. Compared with traditional ceramic tiles, the higher the glossiness, the more delicate it feels, and the lower the glossiness, the rougher it feels. This method of making ceramic tiles can provide low-gloss and delicate tiles to meet the pursuit of more consumer groups.
[0047] The second object of the present invention is to provide a method for preparing the above-mentioned dry particle ceramic tile, comprising the following steps: after water spraying a dried green body, applying a glaze material and an inkjet printing pattern on the surface of the green body in sequence; applying a dry particle glaze slurry on the surface of the green body containing the printed pattern, firing, and grinding the edges to obtain the dry particle ceramic tile;
[0048] The dry granular glaze slurry comprises dry granular glaze, a suspending agent, a protective glaze, a defoaming agent and water.
[0049] Preferably, the preparation method of the dry granular glaze comprises:
[0050] Mixing the raw materials for preparing the dry granular glaze according to weight proportions, and firing the mixture to obtain a fired product;
[0051] The fired product is cooled and crushed to obtain a dry granular semi-finished product;
[0052] The dry granular semi-finished product is treated at a temperature of 850° C. to 950° C. to obtain a dry granular glaze.
[0053] In a specific implementation, the step of processing the dry granule semi-finished product is: heating the dry granule semi-finished product at high temperature in a heating device in a free-falling manner.
[0054] In specific implementation, the protective glaze includes, by mass, 98.5 parts of YFBH frit, 1.5 parts of alumina, 0.07 parts of sodium carboxymethyl cellulose, 0.33 parts of sodium tripolyphosphate, 0.1 parts of preservatives, and 36 parts of water; wherein, the chemical composition of the YFBH frit in the protective glaze includes: 45-51 parts of SiO2, 23-25 parts of Al2O3, 4-5 parts of K2O, 5-6 parts of Na2O, 4-7 parts of CaO, 0.5-1 parts of Li2O, 5-6 parts of SrO, and 5-7 parts of ZnO.
[0055] Preferably, the kiln firing section temperature is between 1180°C and 1210°C.
[0056] Preferably, the specific gravity of the base glaze is 1.8 g / cm 3 -1.9g / cm 3 , flow rate is 30-40s, glaze amount is 400g / m 2 -500g / m 2 The specific gravity of the dry granular glaze is 1.15g / cm 3 -1.2g / cm 3 , flow rate is 30-35s, glaze application amount is 260g / m 2 -310g / m 2 .
[0057] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0058] The experimental methods used in the following examples are conventional methods unless otherwise specified. The materials, reagents, methods and instruments used are conventional materials, reagents, methods and instruments in the art unless otherwise specified, and can be obtained through commercial channels by those skilled in the art.
[0059] Example 1
[0060] This embodiment provides a dry granular tile, and the specific preparation method is as follows:
[0061] (1) Conventional green body pressing and drying, the moisture content of the green body after drying is controlled within 0.3 parts.
[0062] (2) Preparation of glaze: Weigh the raw materials of each component according to the composition of the raw materials of the glaze, wherein the raw materials include the following components in parts by weight: 20 parts of selected potassium feldspar, 15 parts of air knife clay, 22 parts of sodium feldspar, 20 parts of nepheline powder, 4 parts of wollastonite powder, 8 parts of aluminum oxide, 20 parts of quartz powder, 10 parts of zirconium silicate, 3 parts of zinc oxide, 5 parts of 1816 frit, 0.15 parts of thickener, and 0.35 parts of dispersant. The above raw materials are mixed with a total amount of 40 parts of water, and after grinding, sieving, iron removal and other processes, the glaze slurry with a fineness of 0.8 parts to 1 parts is obtained through a 325 mesh sieve, and then aged to obtain the glaze. Among them, the thickener can be selected from conventional commercial products such as methyl cellulose, and the dispersant can be selected from conventional commercial products such as sodium tripolyphosphate, which are not described in detail here. The chemical composition of the above-mentioned glaze includes, by percentage, 56 parts of SiO2, 27 parts of Al2O3, 4 parts of CaO, 6.5 parts of SrO, 4.2 parts of ZnO, 0.03 parts of TiO2, and 3.5 parts of BaO.
[0063] (3) Preparation of dry granular glaze layer:
[0064] ① Preparation of dry particles: weigh the raw materials of each component according to the composition of the raw materials of the dry granular glaze, and the raw materials include the following components in parts by weight: 18 parts of aluminum oxide, 10 parts of calcite, 5 parts of potassium carbonate, 10.5 parts of soda ash, 55 parts of quartz powder, 0.5 parts of zinc oxide, 1 part of strontium carbonate and 3 parts of dolomite; mix the above raw materials, put them into a mixer for stirring, and then sinter them;
[0065] Firing process: heat to 285℃ for 10min, then heat to 1150℃ for 35min after the moisture in the material is fully oxidized, then heat to 1450℃ for 20min, then keep at 1450℃ for 10min, and finally cool to 350-400℃;
[0066] The moisture content of the dry granule semi-finished product is controlled below 1%, and the dry granule semi-finished product is conveyed to the roller mill for crushing. The crushed fine powder is passed through a 250-mesh sieve, and the dry granule fine powder in the 250-mesh range is taken. The rest that is larger than the required mesh number needs to be crushed again until it reaches the qualified mesh number.
[0067] The fine powder dry particles passing through 300 mesh are sprayed into the high-temperature furnace from the entrance of the high-temperature furnace through a cyclone for spheroidization. The temperature of the heating zone is 850°C. Then they enter the equipment for fine treatment such as screening and ball milling, and pass through a sieve of 300-400 mesh to obtain dry granular products.
[0068] The chemical composition of the dry particles is calculated by percentage: 59.52 parts of SiO2, 19.67 parts of Al2O3, 4.31 parts of K2O, 6.85 parts of CaO, 0.81 parts of SrO, 6.72 parts of Na2O, 1.07 parts of ZnO, 0.72 parts of MgO, 1.5 parts of ZrSiO4;
[0069] ② Add 20 parts of the above-mentioned dry particles, 75 parts of suspending agent, 4 parts of water, 2 parts of protective glaze, and 400 grams of defoaming agent to the dry particle glaze and mix thoroughly to obtain dry particle glaze slurry.
[0070] (4) Apply glaze on the surface of the body by pouring or spraying glaze to form a glaze layer with a glaze specific gravity of 1.85g / cm 3 , flow rate is 35s, glaze application amount is 450g / m 2 .
[0071] (5) Inkjet printing patterns on the surface of the glaze layer to form a printing layer.
[0072] (6) Apply dry granular glaze slurry on the surface of the pattern layer by pouring glaze to form a dry granular glaze layer, 1.18g / cm 3 , flow rate is 32s, glaze application amount is 280g / m 2 .
[0073] (7) Firing: The glazed body is fired in a kiln at a maximum temperature of 1210 degrees, and finally the edges are ground to obtain the product.
[0074] The tiles made in this embodiment are as follows Figure 1 shown.
[0075] Example 2
[0076] This embodiment provides a dry granular tile, and the specific preparation method is as follows:
[0077] (1) Conventional green body pressing and drying, the moisture content of the green body after drying is controlled within 0.3 parts.
[0078] (2) Preparation of glaze: Weigh the raw materials of each component according to the composition of the raw materials of the glaze, wherein the raw materials include the following components in parts by weight: 20 parts of selected potassium feldspar, 8 parts of air knife clay, 22 parts of sodium feldspar, 15 parts of nepheline powder, 4 parts of wollastonite powder, 10 parts of aluminum oxide, 15 parts of quartz powder, 10 parts of zirconium silicate, 3 parts of zinc oxide, 5 parts of 1816 frit, 0.15 parts of thickener, and 0.35 parts of dispersant. The above raw materials are mixed with a total amount of 40 parts of water, and after grinding, sieving, iron removal and other processes, a glaze slurry with a fineness of 0.8 parts to 1 parts is obtained through a 325-mesh sieve, and then aged to obtain the glaze. Among them, the thickener can be a conventional commercial product such as methyl cellulose, and the dispersant can be a conventional commercial product such as sodium tripolyphosphate, which are not described in detail here. The chemical composition of the above-mentioned glaze includes, by percentage, 52 parts of SiO2, 24 parts of Al2O3, 6.5 parts of CaO, 7.5 parts of SrO, 6.2 parts of ZnO, 0.03 parts of TiO2, and 5 parts of BaO.
[0079] (3) Preparation of dry granular glaze layer:
[0080] ① Preparation of dry particles: weigh the raw materials of each component according to the composition of the raw materials of the dry particle glaze, and the raw materials include the following components in parts by weight: 17.5 parts of aluminum oxide, 12 parts of calcite, 6 parts of potassium carbonate, 12 parts of soda ash, 47 parts of quartz powder, 0.5 parts of zinc oxide, 1 part of strontium carbonate and 4 parts of dolomite; mix the above raw materials, put them into a mixer for stirring, and then sinter them;
[0081] Firing process: heat to 285℃ for 10min, then heat to 1150℃ for 35min after the moisture in the material is fully oxidized, then heat to 1450℃ for 20min, then keep at 1450℃ for 10min, and finally cool to 350-400℃;
[0082] The moisture content of the dry granule semi-finished product is controlled below 1%, and the dry granule semi-finished product is conveyed to the roller mill for crushing. The crushed fine powder is passed through a 250-mesh sieve, and the dry granule fine powder in the 250-mesh range is taken. The rest that is larger than the required mesh number needs to be crushed again until it reaches the qualified mesh number.
[0083] The fine powder dry particles passing through 300 mesh are sprayed into the high-temperature furnace from the entrance of the high-temperature furnace through a cyclone for spheroidization. The temperature of the heating zone is 850°C. Then they enter the equipment for fine treatment such as screening and ball milling, and pass through a sieve of 300-400 mesh to obtain dry granular products.
[0084] The chemical composition of the dry particles is calculated by percentage: 57.52 parts of SiO2, 18.67 parts of Al2O3, 5.31 parts of K2O, 7.85 parts of CaO, 0.81 parts of SrO, 7 parts of Na2O, 0.85 parts of ZnO, 1 part of MgO, and 1.5 parts of ZrSiO4.
[0085] ② Add 20 parts of the above-mentioned dry particles, 75 parts of suspending agent, 4 parts of water, 2 parts of protective glaze, and 400 grams of defoaming agent to the dry particle glaze and mix thoroughly to obtain dry particle glaze slurry.
[0086] (4) Apply glaze on the surface of the body by pouring or spraying glaze to form a glaze layer with a glaze specific gravity of 1.85g / cm 3 , flow rate is 35s, glaze application amount is 450g / m 2 .
[0087] (5) Inkjet printing patterns on the surface of the glaze layer to form a printing layer.
[0088] (6) Apply dry granular glaze slurry on the surface of the pattern layer by pouring glaze to form a dry granular glaze layer, 1.18g / cm 3 , flow rate is 32s, glaze application amount is 280g / m 2 .
[0089] (7) Firing: The glazed body is fired in a kiln at a maximum temperature of 1220 degrees, and finally the edges are ground to obtain the product.
[0090] The tiles made in this embodiment are as follows Figure 2 shown.
[0091] Example 3
[0092] This embodiment provides a dry granular tile, and the specific preparation method is as follows:
[0093] (1) Conventional green body pressing and drying, the moisture content of the green body after drying is controlled within 0.3 parts.
[0094] (2) Preparation of glaze: Weigh the raw materials of each component according to the composition of the raw materials of the glaze, wherein the raw materials include the following components in parts by weight: 20 parts of selected potassium feldspar, 15 parts of air knife clay, 22 parts of A11 sodium feldspar, 22 parts of nepheline powder H2, 4 parts of wollastonite powder, 8 parts of aluminum oxide, 20 parts of quartz powder, 10 parts of zirconium silicate, 3 parts of zinc oxide, 5 parts of 1816 frit, 0.15 parts of thickener, and 0.35 parts of dispersant. The above raw materials are mixed with a total amount of 40 parts of water, and after grinding, sieving, iron removal and other processes, the glaze slurry with a fineness of 0.8 parts to 1 parts is obtained through a 325 mesh sieve, and then aged to obtain the glaze. Among them, the thickener can be selected from conventional commercial products such as methyl cellulose, and the dispersant can be selected from conventional commercial products such as sodium tripolyphosphate, which are not described in detail here. The chemical composition of the above-mentioned glaze, calculated by weight percentage, includes: 53.5 parts of SiO2, 25.5 parts of Al2O3, 5.5 parts of CaO, 6.5 parts of SrO, 5.2 parts of ZnO, 0.03 parts of TiO2, and 4.5 parts of BaO.
[0095] (3) Preparation of dry granular glaze layer:
[0096] ① Preparation of dry particles: weigh the raw materials of each component according to the composition of the raw materials of the dry particle glaze, and the raw materials include the following components in parts by weight: 17 parts of aluminum oxide, 8 parts of calcite, 7 parts of potassium carbonate, 11 parts of soda ash, 47 parts of quartz powder, 0.5 parts of zinc oxide, 1 part of strontium carbonate and 4 parts of dolomite; mix the above raw materials, put them into a mixer for stirring, and then sinter them;
[0097] Firing process: heat to 285℃ for 10min, then heat to 1150℃ for 35min after the moisture in the material is fully oxidized, then heat to 1450℃ for 20min, then keep at 1450℃ for 10min, and finally cool to 350-400℃;
[0098] The moisture content of the dry granule semi-finished product is controlled below 1%, and the dry granule semi-finished product is conveyed to the roller mill for crushing. The crushed fine powder is passed through a 250-mesh sieve, and the dry granule fine powder in the 250-mesh range is taken. The rest that is larger than the required mesh number needs to be crushed again until it reaches the qualified mesh number.
[0099] The fine powdered dry particles that pass through 300 mesh are sprayed into the high-temperature furnace from the entrance of the high-temperature furnace through a cyclone, and are passed through the heating zone in a free-fall manner for dew drop treatment. The temperature of the heating zone is 850°C, and then enter the equipment for fine treatment such as screening and ball milling, and are screened through a 300-400 mesh screen to obtain dry granular finished products.
[0100] The chemical composition of the dry particles is calculated in percentage as follows: 58.62 parts of SiO2, 19 parts of Al2O3, 5.11 parts of K2O, 7.35 parts of CaO, 0.81 parts of SrO, 6.6 parts of Na2O, 0.85 parts of ZnO, 1 part of MgO, and 1.5 parts of ZrSiO4.
[0101] ② Add 20 parts of the above-mentioned dry particles, 75 parts of suspending agent, 4 parts of water, 2 parts of protective glaze, and 400 grams of defoaming agent to the dry particle glaze and mix thoroughly to obtain dry particle glaze slurry.
[0102] (4) Apply glaze on the surface of the body by pouring or spraying glaze to form a glaze layer with a glaze specific gravity of 1.85g / cm 3 , flow rate is 35s, glaze application amount is 450g / m 2 .
[0103] (5) Inkjet printing patterns on the surface of the glaze layer to form a printing layer.
[0104] (6) Apply dry granular glaze slurry on the surface of the pattern layer by pouring glaze to form a dry granular glaze layer, 1.18g / cm 3 , flow rate is 32s, glaze application amount is 280g / m2 .
[0105] (7) Firing: The glazed body is fired in a kiln at a maximum temperature of 1230 degrees, and finally the edges are ground to obtain the product.
[0106] The tiles made in this embodiment are as follows Figure 3 shown.
[0107] Example 4
[0108] This embodiment provides a dry granular tile, and the specific preparation method is as follows:
[0109] (1) Conventional green body pressing and drying, the moisture content of the green body after drying is controlled within 0.3 parts.
[0110] (2) Preparation of glaze: Weigh the raw materials of each component according to the composition of the raw materials of the glaze, wherein the raw materials include the following components in parts by weight: 20 parts of selected potassium feldspar, 15 parts of air knife clay, 22 parts of sodium feldspar, 20 parts of nepheline powder, 4 parts of wollastonite powder, 8 parts of aluminum oxide, 20 parts of quartz powder, 10 parts of zirconium silicate, 3 parts of zinc oxide, 5 parts of 1816 frit, 0.15 parts of thickener, and 0.35 parts of dispersant. The above raw materials are mixed with a total amount of 40 parts of water, and after grinding, sieving, iron removal and other processes, the glaze slurry with a fineness of 0.8 parts to 1 parts is obtained through a 325 mesh sieve, and then aged to obtain the glaze. Among them, the thickener can be selected from conventional commercial products such as methyl cellulose, and the dispersant can be selected from conventional commercial products such as sodium tripolyphosphate, which are not described in detail here. The chemical composition of the above-mentioned glaze includes, by percentage, 57 parts of SiO2, 27.5 parts of Al2O3, 4 parts of CaO, 5.5 parts of SrO, 4.2 parts of ZnO, 0.03 parts of TiO2, and 3 parts of BaO.
[0111] (3) Preparation of dry granular glaze layer:
[0112] ① Preparation of dry particles: weigh the raw materials of each component according to the composition of the raw materials of the dry granular glaze, and the raw materials include the following components in parts by weight: 20 parts of aluminum oxide, 12 parts of calcite, 5 parts of potassium carbonate, 10.5 parts of soda ash, 55 parts of quartz powder, 0.5 parts of zinc oxide, 1 part of strontium carbonate and 3 parts of dolomite; mix the above raw materials, put them into a mixer for stirring, and then sinter them;
[0113] Firing process: heat to 285℃ for 10min, then heat to 1150℃ for 35min after the moisture in the material is fully oxidized, then heat to 1450℃ for 20min, then keep at 1450℃ for 10min, and finally cool to 350-400℃;
[0114] The moisture content of the dry granule semi-finished product is controlled below 1%, and the dry granule semi-finished product is conveyed to the roller mill for crushing. The crushed fine powder is passed through a 250-mesh sieve, and the dry granule fine powder in the 250-mesh range is taken. The rest that is larger than the required mesh number needs to be crushed again until it reaches the qualified mesh number.
[0115] The fine powder dry particles passing through 300 mesh are sprayed into the high-temperature furnace from the entrance of the high-temperature furnace through a cyclone for spheroidization. The temperature of the heating zone is 850°C. Then they enter the equipment for fine treatment such as screening and ball milling, and pass through a sieve of 300-400 mesh to obtain dry granular products.
[0116] The chemical composition of the dry particles is calculated by percentage: 58.52 parts of SiO2, 20 parts of Al2O3, 4.31 parts of K2O, 5.85 parts of CaO, 0.81 parts of SrO, 7 parts of Na2O, 0.67 parts of ZnO, 0.6 parts of MgO, 1.5 parts of ZrSiO4;
[0117] ② Add 20 parts of the above-mentioned dry particles, 75 parts of suspending agent, 4 parts of water, 2 parts of protective glaze, and 400 grams of defoaming agent to the dry particle glaze and mix thoroughly to obtain dry particle glaze slurry.
[0118] (4) Apply glaze on the surface of the body by pouring or spraying glaze to form a glaze layer with a glaze specific gravity of 1.85g / cm 3 , flow rate is 35s, glaze application amount is 450g / m 2 .
[0119] (5) Inkjet printing patterns on the surface of the glaze layer to form a printing layer.
[0120] (6) Apply dry granular glaze slurry on the surface of the pattern layer by pouring glaze to form a dry granular glaze layer, 1.18g / cm 3 , flow rate is 32s, glaze application amount is 280g / m 2 .
[0121] (7) Firing: The glazed body is fired in a kiln at a maximum temperature of 1210 degrees, and finally the edges are ground to obtain the product.
[0122] The tiles made in this embodiment are as follows Figure 4 shown.
[0123] Comparative Example 1
[0124] This embodiment provides a dry granular tile, and the specific preparation method is as follows:
[0125] (1) Conventional green body pressing and drying, the moisture content of the green body after drying is controlled within 0.3 parts.
[0126] (2) Preparation of glaze: Weigh the raw materials of each component according to the composition of the raw materials of the glaze, wherein the raw materials include the following components in parts by weight: 25 parts of selected potassium feldspar, 10 parts of air knife clay, 22 parts of sodium feldspar, 20 parts of nepheline powder, 5 parts of wollastonite powder, 8 parts of aluminum oxide, 8 parts of quartz powder, 10 parts of zirconium silicate, 3 parts of zinc oxide, 5 parts of 1816 frit, 0.15 parts of thickener, and 0.35 parts of dispersant. The above raw materials are mixed with a total amount of 40 parts of water, and after grinding, sieving, iron removal and other processes, the glaze slurry with a fineness of 0.8 parts to 1 parts is obtained through a 325-mesh sieve, and then aged to obtain the glaze. Among them, the thickener can be selected from conventional commercial products such as methyl cellulose, and the dispersant can be selected from conventional commercial products such as sodium tripolyphosphate, which are not described in detail here. The chemical composition of the above-mentioned glaze includes, by percentage, 48 parts of SiO2, 18 parts of Al2O3, 10 parts of CaO, 9.5 parts of SrO, 7.2 parts of ZnO, 0.03 parts of TiO2, and 6.5 parts of BaO.
[0127] (3) Preparation of dry granular glaze layer:
[0128] ① Preparation of dry particles: weigh the raw materials of each component according to the composition of the raw materials of the dry granular glaze, and the raw materials include the following components in parts by weight: 18 parts of aluminum oxide, 10 parts of calcite, 5 parts of potassium carbonate, 10.5 parts of soda ash, 55 parts of quartz powder, 0.5 parts of zinc oxide, 1 part of strontium carbonate and 3 parts of dolomite; mix the above raw materials, put them into a mixer for stirring, and then sinter them;
[0129] Firing process: heat to 285℃ for 10min, then heat to 1150℃ for 35min after the moisture in the material is fully oxidized, then heat to 1450℃ for 20min, then keep at 1450℃ for 10min, and finally cool to 350-400℃;
[0130] The moisture content of the dry granule semi-finished product is controlled below 1%, and the dry granule semi-finished product is conveyed to the roller mill for crushing. The crushed fine powder is passed through a 250-mesh sieve, and the dry granule fine powder in the 250-mesh range is taken. The rest that is larger than the required mesh number needs to be crushed again until it reaches the qualified mesh number.
[0131] The fine powdered dry particles that pass through 300 mesh are sprayed into the high-temperature furnace from the entrance of the high-temperature furnace through a cyclone, and are passed through the heating zone in a free-fall manner for dew drop treatment. The temperature of the heating zone is 850°C, and then enter the equipment for fine treatment such as screening and ball milling, and are screened through a 300-400 mesh screen to obtain dry granular finished products.
[0132] The chemical composition of the dry particles is calculated by percentage: 59.52 parts of SiO2, 19.67 parts of Al2O3, 4.31 parts of K2O, 6.85 parts of CaO, 0.81 parts of SrO, 6.72 parts of Na2O, 1.07 parts of ZnO, 0.72 parts of MgO, 1.5 parts of ZrSiO4;
[0133] ② Add 20 parts of the above-mentioned dry particles, 75 parts of suspending agent, 4 parts of water, 2 parts of protective glaze, and 400 grams of defoaming agent to the dry particle glaze and mix thoroughly to obtain dry particle glaze slurry.
[0134] (4) Apply glaze on the surface of the body by pouring or spraying glaze to form a glaze layer with a glaze specific gravity of 1.85g / cm 3 , flow rate is 35s, glaze application amount is 450g / m 2 .
[0135] (5) Inkjet printing patterns on the surface of the glaze layer to form a printing layer.
[0136] (6) Apply dry granular glaze slurry on the surface of the pattern layer by pouring glaze to form a dry granular glaze layer, 1.18g / cm 3 , flow rate is 32s, glaze application amount is 280g / m 2 .
[0137] (7) Firing: The glazed body is fired in a kiln at a maximum temperature of 1210 degrees, and finally the edges are ground to obtain the product.
[0138] The tiles made in this embodiment are as follows Figure 5 shown.
[0139] Comparative Example 2
[0140] This embodiment provides a dry granular tile, and the specific preparation method is as follows:
[0141] (1) Conventional green body pressing and drying, the moisture content of the green body after drying is controlled within 0.3 parts.
[0142] (2) Preparation of glaze: Weigh the raw materials of each component according to the composition of the raw materials of the glaze, wherein the raw materials include the following components in parts by weight: 25 parts of selected potassium feldspar, 10 parts of air knife clay, 22 parts of A11 sodium feldspar, 20 parts of nepheline powder H2, 5 parts of wollastonite powder, 8 parts of aluminum oxide, 8 parts of quartz powder, 10 parts of zirconium silicate, 3 parts of zinc oxide, 5 parts of 1816 frit, 0.15 parts of thickener, and 0.35 parts of dispersant. The above raw materials are mixed with a total amount of 40 parts of water, and after grinding, sieving, iron removal and other processes, a glaze slurry with a fineness of 0.8 parts to 1 parts is obtained through a 325-mesh sieve, and then aged to obtain the glaze. Among them, the thickener can be selected from conventional commercial products such as methyl cellulose, and the dispersant can be selected from conventional commercial products such as sodium tripolyphosphate, which are not described in detail here. The chemical composition of the above-mentioned glaze includes, by percentage, 58.6 parts of SiO2, 29.2 parts of Al2O3, 3.2 parts of CaO, 4.5 parts of SrO, 2.95 parts of ZnO, 0.03 parts of TiO2, and 3.2 parts of BaO.
[0143] (3) Preparation of dry granular glaze layer:
[0144] ① Preparation of dry particles: weigh the raw materials of each component according to the composition of the raw materials of the dry particle glaze, and the raw materials include the following components in parts by weight: 16 parts of potassium feldspar, 44 parts of sodium feldspar, 5 parts of dolomite, 15 parts of barium carbonate, 10 parts of wollastonite, 5 parts of zinc oxide, 5 parts of strontium carbonate, 15 parts of quartz, 5 parts of air knife clay and 7 parts of aluminum oxide; mix the above raw materials, put them into a mixer for stirring, and then sinter them;
[0145] Firing process: heat to 285℃ for 10min, then heat to 1150℃ for 35min after the moisture in the material is fully oxidized, then heat to 1450℃ for 20min, then keep at 1450℃ for 10min, and finally cool to 350-400℃;
[0146] The moisture content of the dry granule semi-finished product is controlled below 1%, and the dry granule semi-finished product is conveyed to the roller mill for crushing. The crushed fine powder is passed through a 250-mesh sieve, and the dry granule fine powder in the 250-mesh range is taken. The rest that is larger than the required mesh number needs to be crushed again until it reaches the qualified mesh number.
[0147] The fine powdered dry particles that pass through 300 mesh are sprayed into the high-temperature furnace from the entrance of the high-temperature furnace through a cyclone, and are passed through the heating zone in a free-fall manner for dew drop treatment. The temperature of the heating zone is 850°C, and then enter the equipment for fine treatment such as screening and ball milling, and are screened through a 300-400 mesh screen to obtain dry granular finished products.
[0148] The chemical composition of the dry particles is calculated by percentage: 65.52 parts SiO2, 21 parts Al2O3, 4.31 parts K2O, 5.85 parts CaO, 0.81 parts SrO, 4.5 parts Na2O, 0.5 parts ZnO, 0.5 parts MgO, 1 part ZrSiO4
[0149] ② Add 20 parts of the above-mentioned dry particles, 75 parts of suspending agent, 4 parts of water, 2 parts of protective glaze, and 400 grams of defoaming agent to the dry particle glaze in a ratio of 100 kg and 400 grams, and mix thoroughly to obtain dry particle glaze slurry.
[0150] (4) Apply glaze on the surface of the body by pouring or spraying glaze to form a glaze layer with a glaze specific gravity of 1.85g / cm 3 , flow rate is 35s, glaze application amount is 450g / m 2 .
[0151] (5) Inkjet printing patterns on the surface of the glaze layer to form a printing layer.
[0152] (6) Apply dry granular glaze slurry on the surface of the pattern layer by pouring glaze to form a dry granular glaze layer, 1.18g / cm 3 , flow rate is 32s, glaze application amount is 280g / m 2 .
[0153] (7) Firing: The glazed body is fired in a kiln at a maximum temperature of 1210 degrees, and finally the edges are ground to obtain the product.
[0154] The tiles made in this embodiment are as follows Figure 6 shown.
[0155] Comparative Example 3
[0156] This embodiment provides a dry granular tile, and the specific preparation method is as follows:
[0157] (1) Conventional green body pressing and drying, the moisture content of the green body after drying is controlled within 0.3 parts.
[0158] (2) Preparation of glaze: Weigh the raw materials of each component according to the composition of the raw materials of the glaze, wherein the raw materials include the following components in parts by weight: 25 parts of selected potassium feldspar, 10 parts of air knife clay, 22 parts of A11 sodium feldspar, 20 parts of nepheline powder H2, 5 parts of wollastonite powder, 8 parts of aluminum oxide, 8 parts of quartz powder, 10 parts of zirconium silicate, 3 parts of zinc oxide, 5 parts of 1816 frit, 0.15 parts of thickener, and 0.35 parts of dispersant. The above raw materials are mixed with a total amount of 40 parts of water, and after grinding, sieving, iron removal and other processes, a glaze slurry with a fineness of 0.8 parts to 1 parts is obtained through a 325-mesh sieve, and then aged to obtain the glaze. Among them, the thickener can be selected from conventional commercial products such as methyl cellulose, and the dispersant can be selected from conventional commercial products such as sodium tripolyphosphate, which are not described in detail here. The chemical composition of the above-mentioned glaze includes, by percentage, 61 parts of SiO2, 30 parts of Al2O3, 3 parts of CaO, 5.5 parts of SrO, 3.2 parts of ZnO, 0.03 parts of TiO2, and 3.5 parts of BaO.
[0159] (3) Preparation of dry granular glaze layer:
[0160] ① Preparation of dry particles: weigh the raw materials of each component according to the composition of the raw materials of the dry particle glaze, and the raw materials include the following components in parts by weight: 16 parts of potassium feldspar, 44 parts of sodium feldspar, 5 parts of dolomite, 15 parts of barium carbonate, 10 parts of wollastonite, 5 parts of zinc oxide, 5 parts of strontium carbonate, 15 parts of quartz, 5 parts of air knife clay and 7 parts of aluminum oxide; mix the above raw materials, put them into a mixer for stirring, and then sinter them;
[0161] Firing process: heat to 285℃ for 10min, then heat to 1150℃ for 35min after the moisture in the material is fully oxidized, then heat to 1450℃ for 20min, then keep at 1450℃ for 10min, and finally cool to 350-400℃;
[0162] The moisture content of the dry granule semi-finished product is controlled below 1%, and the dry granule semi-finished product is conveyed to the roller mill for crushing. The crushed fine powder is passed through a 250-mesh sieve, and the dry granule fine powder in the 250-mesh range is taken. The rest that is larger than the required mesh number needs to be crushed again until it reaches the qualified mesh number.
[0163] The fine powdered dry particles that pass through 300 mesh are sprayed into the high-temperature furnace from the entrance of the high-temperature furnace through a cyclone, and are passed through the heating zone in a free-fall manner for dew drop treatment. The temperature of the heating zone is 850°C, and then enter the equipment for fine treatment such as screening and ball milling, and are screened through a 300-400 mesh screen to obtain dry granular finished products.
[0164] The chemical composition of the dry particles is calculated by percentage: 66.23 parts of SiO2, 21.6 parts of Al2O3, 4.21 parts of K2O, 6.25 parts of CaO, 0.81 parts of SrO, 6 parts of Na2O, 0.5 parts of ZnO, 0.5 parts of MgO, 1 part of ZrSiO4. ② Add 20 parts of the above dry particles, 75 parts of suspending agent, 4 parts of water, 2 parts of protective glaze, and 100 kg of defoaming agent plus 400 grams of dry particle glaze and mix thoroughly to obtain dry particle glaze slurry.
[0165] (4) Apply glaze on the surface of the body by pouring or spraying glaze to form a glaze layer with a glaze specific gravity of 1.85g / cm 3 , flow rate is 35s, glaze application amount is 450g / m 2 .
[0166] (5) Inkjet printing patterns on the surface of the glaze layer to form a printing layer.
[0167] (6) Apply dry granular glaze slurry on the surface of the pattern layer by pouring glaze to form a dry granular glaze layer, 1.18g / cm 3 , flow rate is 32s, glaze application amount is 280g / m 2 .
[0168] (7) Firing: The glazed body is fired in a kiln at a maximum temperature of 1210 degrees, and finally the edges are ground to obtain the product.
[0169] The tiles made in this embodiment are as follows Figure 7 shown.
[0170] Test Example 1
[0171] Temperature stability test
[0172] Test samples: a dry granular ceramic provided in Examples 1-4, and a ceramic provided in Comparative Examples 1-3;
[0173] Test standard: This experiment uses a WGG60-E4 type photometer. After starting up, use a standard plate to adjust the 0 gloss point and the highlight 97.0 degree point. Then place the glossmeter on the sample to be tested to obtain the gloss data. According to national standards, the test results of the above embodiments and comparative examples at different temperatures are shown in Table 1; determined by touch feel, excellent 10 points, relatively good 7-9 points, generally 4-6 points, poor 1-3 points; the higher the score, the better the feel, preferably greater than 7 points, the test results of the above embodiments and comparative examples are shown in Table 2:
[0174] Table 1 Glossiness test
[0175] Firing temperature 1210℃ 1220℃ 1230℃ 1235℃ Example 1 10.5 degrees 11 degrees 11.5 degrees 13 degrees Example 2 11 degrees 12 degrees 12 degrees 13 degrees Example 3 10.5 degrees 10.5 degrees 12 degrees 12.5 degrees Example 4 10.5 degrees 11 degrees 11.5 degrees 12 degrees Comparative Example 1 19 degrees 21 degrees 24 degrees 26 degrees Comparative Example 2 7 degrees 7.5 degrees 9 degrees 10 degrees Comparative Example 3 4 degrees 5 degrees 6.5 degrees 8 degrees
[0176] Table 2 Hand feel evaluation
[0177] Firing temperature 1210℃ 1220℃ 1230℃ 1235℃ Example 1 8.5 points 8.5 points 10 points 10 points Example 2 9 points 10 points 10 points 10 points Example 3 9 points 9 points 10 points 10 points Example 4 9 points 9.5 points 10 points 10 points Comparative Example 1 8 points 8 points 8 points 6 points Comparative Example 2 5 points 6 points 6 points 7 points Comparative Example 3 4 points 4.5 points 5 points 6 points
[0178] It can be seen from the test data in Table 1 above that the ceramic tiles prepared by the technical solution of the present invention have little difference in product performance when fired within a large temperature range and have temperature stability.
[0179] Reference Figure 1-7 It can be seen that the surface gloss of the ceramic tiles of Examples 1-4 is lower than that of Comparative Example 1, and the surface gloss of the ceramic tiles of Examples 1-4 is higher than that of Comparative Examples 2-3. The ceramic tiles prepared using the technical solution of the present invention have a glossiness between 10 and 20 degrees relative to the comparative examples, feel smooth and unobstructed, and have a better texture than traditional ceramic tiles.
[0180] Referring to Table 1 and Table 2, it can be seen from the comparison between Example 1 and Comparative Example 1 that the difference between Comparative Example 1 and Example 1 is only the formula of the glaze. From the perspective of chemical composition percentage, the proportion of SiO2 and Al2O3 in Example 1 is 56 parts of SiO2 and 27 parts of Al2O3, while the proportion of Comparative Example 1 is only 48 parts of SiO2 and 18 parts of Al2O3. The reduced proportions of SiO2 and Al2O3 are proportionally distributed to other raw materials. The silicon and aluminum content of Comparative Example 1 is less than the silicon and aluminum content range specified in the present invention.
[0181] The glossiness of the ceramic tile of Example 1 is relatively stable at a firing temperature of 1210°C-1235°C, with a difference of only 2-2.5, and has temperature stability, while the glossiness difference of the ceramic tile provided by Comparative Example 1 is 7, and the temperature stability is poor; in addition, at a firing temperature of 1210°C-1235°C, the hand feel of the ceramic tile provided by Example 1 is greater than 8 points, while the hand feel of the ceramic tile provided by Comparative Example 1 is poor at 1235°C. This shows that when the content of SiO2 and Al2O3 in the glaze is less than 50 parts SiO2 and 20 parts Al2O3, the temperature stability of the ceramic tile obtained is poor and the hand feel is poor.
[0182] From the comparison between Examples 1-4 and Comparative Examples 2-3, it can be seen that the contents of SiO2 and Al2O3 in the dry granular glazes of Examples 1-4 are between 58 parts and 65 parts of SiO2 and 15 parts and 20 parts of Al2O3, and the contents of SiO2 and Al2O3 in the surface glazes are between 50 parts and 58 parts of SiO2 and 20 parts and 28 parts of Al2O3, while the dry granular glaze of Comparative Example 2 contains 65.23 parts of SiO2 and 21 parts of Al2O3, and the surface glaze contains 20 parts and 28 parts of Al2O3. The material contains 58.6 parts of SiO2 and 29.2 parts of Al2O3. The dry granular glaze of Comparative Example 3 contains 66.23 parts of SiO2 and 21.6 parts of Al2O3, and the surface glaze contains 61 parts of SiO2 and 30 parts of Al2O3. The silicon aluminum content of Comparative Examples 2-3 is greater than the silicon aluminum content range specified in the present invention, and the gloss difference of Comparative Examples 2-3 is larger than that of Examples 1-4 at a firing temperature of 1210°C-1235°C, and the feel evaluation is lower.
[0183] This shows that when the silicon-aluminum content exceeds 65 parts of SiO2 and 20 parts of Al2O3 in the dry particle glaze and 58 parts of SiO2 and 28 parts of Al2O3 in the surface glaze, the resulting tiles have poor temperature stability and poor feel.
[0184] In summary, if the silicon and aluminum content in the dry granular glaze and the surface glaze is lower than the range specified in the present invention or higher than the range specified in the present invention, it will lead to poor temperature stability and hand feel. The glossiness of the tiles prepared by the technical solution of the present invention is between 10-15 degrees, with little limitation on production conditions, temperature stability, and better hand feel than comparative examples 1-3.
[0185] Test Example 2
[0186] Stain resistance and anti-slip performance testing
[0187] Test samples: a dry granular ceramic provided in Examples 1-4, and a ceramic provided in Comparative Examples 1-3;
[0188] Test standard: GB / T3810.14-2016 method is used to test the surface stain resistance, and DIN51130.2014 method is used to test the surface anti-slip performance;
[0189] The test results are shown in Table 3 below:
[0190] Table 3 Anti-fouling performance and anti-slip performance test
[0191]
[0192] It can be seen from the test data in Table 3 above that the tiles prepared by adopting the technical solution of the present invention have good stain resistance and anti-slip properties.
[0193] From the comparison between Example 1 and Comparative Example 1, it can be seen that the difference between Comparative Example 1 and Example 1 is only the formula of the glaze, and the anti-slip performance of Example 1 is better than that of Comparative Example 1, which indicates that the ceramic tile prepared by the technical solution of the present invention has good anti-slip performance;
[0194] From the comparison between Examples 1-4 and Comparative Examples 2-3, it can be seen that the silicon aluminum content of Comparative Examples 2-3 is greater than the silicon aluminum content range specified in the present invention, while the stain resistance and anti-slip performance of Examples 1-4 are better than those of Comparative Examples 2-3, which indicates that the tiles prepared using the technical solution of the present invention have good stain resistance and anti-slip performance.
[0195] In summary, the silicon and aluminum content in the dry particle glaze and the surface glaze is lower than the range specified in the present invention or higher than the range specified in the present invention, which will lead to poor anti-slip and anti-fouling properties. The tiles prepared using the technical solution of the present invention have better anti-slip and anti-fouling properties than those of comparative examples 1-3.
[0196] The ceramic tile of the present invention forms a stable crystal structure inside the ceramic during the firing process by adjusting the ratio of silicon and aluminum content in the surface glaze and dry particle glaze formula, thereby reducing the degree of influence by external temperature. The ceramics fired at a wide range of temperatures have the same properties and have small production limitations. In addition, the dry particles in the formula have a small particle size and are tightly packed, thus having good anti-fouling and wear resistance. The surface glossiness of the ceramic tile is between 10 and 20 degrees, the surface of the ceramic tile is warm and transparent, the hand feel is delicate and smooth, and the texture is better than that of traditional ceramic tiles.
[0197] In addition, low-gloss ceramics usually have poor surface stain resistance and anti-slip properties. The ceramics of the present invention have a gloss between 10-20 degrees and can also have good stain resistance and anti-slip properties, taking into account both low gloss and stain resistance, and are suitable for various application scenarios.
[0198] Obviously, the above embodiments of the present invention are merely examples for clearly illustrating the technical solution of the present invention, and are not intended to limit the specific implementation methods of the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the claims of the present invention shall be included in the protection scope of the claims of the present invention.
Claims
1. A dry granular tile, characterized in that: The ceramic tile comprises, from bottom to top, a body layer, a surface glaze layer, a printing layer and a dry granular glaze layer, the raw material of the dry granular glaze layer comprises dry granular glaze, and the raw material of the surface glaze layer comprises surface glaze; The chemical composition of the dry granular glaze, in terms of weight percentage, includes: 58-65 parts of SiO2, 15-20 parts of Al2O3, 4.5-6.5 parts of K2O, 5-8 parts of CaO, 0.65-1.56 parts of SrO, 6-8 parts of Na2O, 0.5-0.96 parts of ZnO, 0.5-1.2 parts of MgO, and 1-3 parts of ZrSiO4; The chemical composition of the glaze, calculated by weight percentage, includes: 50-58 parts of SiO2, 20-28 parts of Al2O3, 3-5 parts of CaO, 3-8 parts of SrO, 2-4 parts of ZnO, 0.01-0.03 parts of TiO2, and 1-3 parts of BaO.
2. A dry particle tile according to claim 1, characterized in that: The raw materials of the dry granular glaze include, by weight: 17-20 parts of aluminum oxide, 8-12 parts of calcite, 5-6 parts of potassium carbonate, 8-12 parts of soda ash, 45-56 parts of quartz powder, 0.5-1 parts of zinc oxide, 1-2 parts of strontium carbonate, and 2-4 parts of dolomite.
3. The dry particle tile according to claim 1, characterized in that: The raw materials of the surface glaze include, by weight: 15-22 parts of selected potassium feldspar, 5-10 parts of air knife clay, 15-25 parts of sodium feldspar, 10-20 parts of nepheline powder, 3-10 parts of wollastonite powder, 5-16 parts of aluminum oxide, 12-17 parts of quartz powder, 5-10 parts of zirconium silicate, 1-3 parts of zinc oxide, 5-10 parts of 1816 frit, 0.2-0.5 parts of sodium tripolysulfate, and 0.1-0.2 parts of sodium methyl cellulose.
4. The dry particle ceramic tile according to claim 3, characterized in that: The main components of the selected potassium feldspar are 65-68% SiO2, 16-18% Al2O3, and 13-15% K2O; the 1816 frit includes, by weight: 43-49 parts of SiO2, 24-26 parts of Al2O3, 4-5 parts of K2O, 3-5 parts of Na2O, 4-7 parts of CaO, 0.5-1 parts of Li2O, 4-5 parts of SrO, and 8-10 parts of ZnO.
5. The dry particle tile according to claim 1, characterized in that: The particle size of the dry granular glaze is between 50um and 100um.
6. The dry particle tile according to claim 1, characterized in that: The glossiness of the tile surface is 10-20 degrees.
7. A method for preparing the dry particle ceramic tile according to any one of claims 1 to 6, characterized in that: The following steps are involved: After the dried green body is treated by water spraying, a glaze material and an inkjet printing pattern are sequentially applied on the surface of the green body; Applying dry granular glaze slurry on the surface of the blank containing the printed pattern, firing, and grinding the edges to obtain the dry granular ceramic tile; The dry particle glaze slurry comprises dry particle glaze, suspending agent, protective glaze, defoaming agent and water.
8. The method for preparing dry granular tiles according to claim 7, characterized in that: The preparation method of the dry granular glaze comprises: Mixing the raw materials for preparing the dry granular glaze according to weight proportions, and firing the mixture to obtain a fired product; The fired product is cooled and crushed to obtain a dry granular semi-finished product; The dry granular semi-finished product is treated at a temperature of 850° C. to 950° C. to obtain a dry granular glaze.
9. The method for preparing dry granular tiles according to claim 7, characterized in that: The ratio of the defoamer to the dry granular glaze is (0.05-0.2):
1.
10. The method for preparing dry granular tiles according to claim 7, characterized in that: The kiln firing temperature is 1180℃-1210℃.
Citation Information
Patent Citations
Dry granular glaze, matte ceramic tile and preparation method of dry granular glaze
CN115572067A
Cited By
Anti-lime stone glazed ceramic tile and preparation method thereof
CN121574010A